Musculoskeletal and body composition response to high-dose testosterone with finasteride after chronic incomplete spinal cord injury—a randomized, double-blind, and placebo-controlled pilot study - Otzel, Dana M.; Nichols, Larissa; Conover, Christine F.; Marangi, Stephen A.; Kura, Jayachandra R.; Iannaccone, Dominic K.; Clark, David J.; Gregory, Chris M.; Sonntag, Christopher F.; Wokhlu, Anita; Ghayee, Hans K.; McPhaul, Michael J.; et al. (Frontiers in Neurology, 2024)
BackgroundHigh-dose testosterone replacement therapy (TRT), paired with finasteride (type II 5α-reductase inhibitor), improves body composition, muscle strength, and bone mineral density (BMD) in older men, without inducing prostate enlargement—a side effect associated with TRT. Men with spinal cord injury (SCI) exhibit neuromuscular impairment, muscle atrophy, bone loss, and increased central adiposity, along with low testosterone. However, sparse evidence supports TRT efficacy after SCI.MethodsThis parallel-group, double-blind, placebo-controlled, and randomized clinical trial (RCT) is a pilot study that enrolled men (N = 12) with low to low–normal testosterone and gait impairments after chronic motor-incomplete SCI. Participants received high-dose intramuscular TRT (testosterone-enanthate, 125 mg/week) with finasteride (5 mg/day) vs. vehicle+placebo for 12 months. Change relative to baseline was determined for body composition, musculoskeletal outcomes, and prostate size, with effect sizes calculated between groups using Hedges’ g. Adverse events and feasibility were assessed.ResultsTRT + finasteride consistently increased testosterone (g = 1.16–3.08) and estradiol (g = 0.43–3.48), while concomitantly reducing dihydrotestosterone (g = 0.31–2.27). Very large effect sizes at both 6 and 12 months suggest TRT + finasteride increased whole-body fat-free (lean) mass (+3–4% vs. baseline, g = 2.12–2.14) and knee extensor (KE) whole-muscle cross-sectional area (+8–11% vs. baseline, g = 2.06–2.53) more than vehicle+placebo. Moderate-to-large effect sizes suggest TRT + finasteride increased KE maximal voluntary isometric torque (+15–40% vs. baseline, g = 0.47–1.01) and femoral neck and distal femur BMD from 6 months onward (g = 0.51–1.13), compared with vehicle+placebo, and reduced fat mass 9–14% within the whole-body, trunk, and android (visceral) regions at 12 months (g = 0.77–1.27). TRT + finasteride also produced small effect sizes favoring lesser prostate growth than vehicle+placebo (g = 0.31–0.43). The participant retention, drug compliance, and incidence and severity of adverse events were similar among the groups.ConclusionThese data provide proof-of-concept and rationale for larger RCTs aimed at discerning the impact of TRT + finasteride on body composition, musculoskeletal health, and physical function in men with SCI, along with effect sizes and variance of responses to assist in planning subsequent trials.Clinical trial registrationClinicalTrials.gov, identifier NCT02248701.